Analisis Perbandingan Pengungkapan Dan Pelaksanaan Corporate Social Responsibility Terhadap Pt.Bank Negara Indonesia (Study Kasus pada PT.Bank Negara Indonesia) - Farida Efriyanti; Sarah Genevine; Riswan RISWAN (Universitas Bandar Lampung (UBL), 2012)
This study aims to analyze the comparative disclosure and implementation of Corporate Social Responsibility Bank Negara Indonesia. This study was conducted to analyze how Bank Negara Indonesia, said corporate social responsibility. This study uses a case study of sustainable annual report of Bank Negara Indonesia. Results of this study indicate that social responsibility disclosure in accordance with Bank Negara Indonesia implementation.